Analysis of Backhand Short Serve Movement on Target Accuracy Among Junior Male Badminton Athletes at Angkasa Pura Medan Club - Saragih, Juan Prima; Sagala, Ronaldo; Sitompul, Samuel Calvin (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
This study aims to analyze the accuracy of the short backhand serve among male junior badminton athletes at Angkasa Pura Club Medan. The research seeks to provide insights into the factors influencing serve accuracy and their contribution to match performance. A qualitative approach was employed, involving 30 athletes aged between 13 and 17 years. Data were collected through direct observation during training sessions, semi-structured interviews with 10 athletes and 3 coaches, and accuracy measurements using predefined serve targets. The results show variations in the accuracy of the short backhand serve, influenced by technical, physical, and mental factors. Common errors included lack of concentration and suboptimal technique. From the data analysis, it was concluded that mastery of basic serve techniques significantly impacts accuracy, highlighting the importance of repetitive serve practice. This study aims to provide recommendations for developing training programs in badminton clubs to improve athletes' serving skills.